VALUE MANAGEMENT OF CONSTRUCTION PRODUCTS - A. V. Kozlovsky; O. E. Astafieva; N. A. Moiseenko (Вестник университета)
The issues of cost management from the point of view of substantiating the reduction in the cost of investment products in order to create reasoned conditions for the interest of investors in long-term investments have been considered. The main emphasis on the real economic sector has been made, since it is in this sector that budget revenues at all levels are generated and overall economic growth is ensured. The existing mechanism of cost management in the implementation of investment programs has been assessed. Attention to the main elements of the cost management mechanism in the investment and construction sector of the economy has been paid. Factors that determine the level of production expenses taking into account the specifics of construction products have been analysed. An attempt to justify multi-factor cost management has been made. Management functions by performers have been differentiated.